2013
DOI: 10.1038/onc.2013.300
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic PAK4 regulates Smad2/3 axis involving gastric tumorigenesis

Abstract: The alteration of p21-activated kinase 4 (PAK4) and transforming growth factor-beta (TGF-β) signaling effector Smad2/3 was detected in several types of tumors, which acts as oncogenic factor and tumor suppressor, but the relationship between these events has not been explored. Here, we demonstrate that PAK4 interacts with and modulates phosphorylation of Smad2/3 via both kinase-dependent and kinase-independent mechanisms, which attenuate Smad2/3 axis transactivation and TGF-β-mediated growth inhibition in gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…TGF-β transmits signals to the nucleus via a network of multiprotein complexes using the SMA and mothers against decapentaplegic (MAD; SMAD) family of proteins. Loss of SMAD was correlated to GC susceptibility,140 and HGF activation of PAK4 induced SMAD2 phosphorylation and proteasomal degradation 17. One mechanism in which PAK4 may promote GC metastasis is through the modification of microtubule homeostasis proteins such as superior cervical ganglia 10 (SCG10).…”
Section: Paks In Gi Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β transmits signals to the nucleus via a network of multiprotein complexes using the SMA and mothers against decapentaplegic (MAD; SMAD) family of proteins. Loss of SMAD was correlated to GC susceptibility,140 and HGF activation of PAK4 induced SMAD2 phosphorylation and proteasomal degradation 17. One mechanism in which PAK4 may promote GC metastasis is through the modification of microtubule homeostasis proteins such as superior cervical ganglia 10 (SCG10).…”
Section: Paks In Gi Diseasesmentioning
confidence: 99%
“…Overall, PAK1 and PAK4 are the most investigated of all PAKs, and have been brought into focus due to their association with various malignancies 1. PAK overexpression contributes to tumour invasiveness in uveal melanoma,7 8 neurofibromatosis,9 breast,10 11 cervical,12 colon,13 14 oesophageal,15 gastric,16 17 hepatic,18 lung,19 ovarian,20 prostate21 22 and thyroid cancer 23. PAKs were also correlated to inflammatory diseases such as rheumatoid arthritis24 and asthma 25.…”
Section: Introductionmentioning
confidence: 99%
“…PAK4 expression in human samples or cell lines of gastric cancer has been investigated in other studies 15 17 18. These studies pointed to an underlying oncogenic potential of PAK4.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells that have high PAK4 levels also have mutations in genes in the senescence pathway, such as p53, thus allowing them to undergo transformation rather than senescence 19. PAK4 interacts with Smad2/3 and phosphorylates Smad2/3, thereby impairing the transforming growth factor β1 (TGF-β1) signalling pathway, resulting in escape from TGF-β-mediated growth inhibition in gastric cancer cells 18. DiGeorge critical region 6 (DGCR6L), which may be involved in cancer cell migration and is necessary for PAK4 forming a complex with β-actin, interacts directly with PAK4 and enhances PAK4-mediated migration of human gastric cancer cells through LIMK1 17…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Pak4 was detected in GC as well as several other tumors [11][12][13][14][15]. Recent studies have demonstrated that Pak4 activity promotes cell migration and invasion in GC cell line SGC-7901 through HGF/Pak4/LIMK1/cofilin and MEK/MMP2 pathways [16].…”
Section: Introductionmentioning
confidence: 96%